Grounded theory and inductive ethnography - Uhan, Samo (Teorija in praksa, 2013)
In the last decade the methodology of social research has been experiencing rapid growth. In this process, an important place has increasingly been taken by qualitative research methods which have also been foregrounded in fields that a couple of decades ago were exclusively reserved for quantitative research approaches. In the last few years attempts at merging and combining research approaches have been emerging within triangulation, along with the existence of more ambitious attempts at creating the so-called reflexive methodology. Based on this premise, this paper will address two methods: grounded theory (hereinafter GT) and inductive ethnography, with each of them employing its own specific way of solving quandaries faced by researchers who use qualitative methods in their work. The aim of this paper is to examine the potential of the research complementarity of GT and inductive ethnography in the context of the merging and combining of research approaches. First, we will look for answers by reflexively examining the properties of both approaches' research techniques which in the concluding part of the paper will end by identifying the methodological context enabling the coherent use of the two research approaches.
Keywords: Družboslovna metodologija; družboslovno raziskovanje; Ethnography; Etnografija; Grounded theory; Kvalitativna metoda; metodologija; Qualitative method; Social science methodology; Utemeljena teorija